A high-strength pre-laid waterproofing coiled material and preparation method thereof
By using a combination of polymer coating, modified asphalt self-adhesive layer and polyester tire base layer in the pre-paved waterproof roll, combined with the synergistic effect of nitrile rubber, hydroxy polyester resin and modified silica, the problem of poor peel strength performance of traditional rolls is solved, and the waterproof effect with high strength and long life is achieved.
Patent Information
- Application Number
- CN202410820854.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-24
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-06-24
AI Technical Summary
Traditional prepaved waterproof coils are prone to aging and brittle cracking during use, resulting in poor peeling strength performance from the post-cast concrete, affecting the waterproofing effect and service life.
A high-strength pre-paved waterproof coil consisting of a polymer coating, a first asphalt self-adhesive layer, a polyester tire base layer, a second asphalt self-adhesive layer and an isolation layer is used. By adding nitrile rubber and hydroxy polyester resin to the first asphalt self-adhesive layer, and adding modified silica to the polymer coating, the adhesive effect and peel strength performance of the coil are improved.
It significantly improves the peel strength performance of pre-paved waterproof coil and post-pouring concrete, extends the service life of the coil, and enhances its waterproof effect.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of waterproof materials, and in particular to a high-strength pre-laid waterproof coiled material and a preparation method thereof. Background Art
[0002] Pre-laid waterproofing membrane is a kind of waterproof material, which plays a role in waterproofing and anti-seepage in various industrial and civil buildings and structures. It is even used in various underground projects and waterproofing projects in non-exterior leakage areas. Its main purpose is to provide a waterproof barrier to protect the integrity of structures such as buildings and ensure their service life and comfort of living or working, so that they are not eroded by rain or groundwater. Traditional pre-laid waterproofing membranes are asphalt-based self-adhesive membrane waterproofing membranes, with asphalt self-adhesive adhesive as the self-adhesive layer. Because asphalt adhesive is prone to aging and brittle cracking during use, the peeling strength performance between it and the post-poured concrete is reduced, affecting the use effect and service life of the waterproofing membrane. Therefore, it is necessary to develop a high-strength pre-laid waterproofing membrane to meet the needs of the project and achieve protection of the building. Summary of the invention
[0003] The present invention provides a high-strength pre-laid waterproofing membrane and a preparation method thereof, which solves the problem of poor peeling strength performance between the pre-laid waterproofing membrane and post-cast concrete in the related art.
[0004] The technical solution of the present invention is as follows:
[0005] A high-strength pre-laid waterproofing coiled material comprises a polymer coating, a first asphalt self-adhesive layer, a polyester base layer, a second asphalt self-adhesive layer and an isolation layer arranged in sequence from top to bottom, wherein the raw materials of the polymer coating comprise the following components in parts by weight:
[0006] 30-50 parts of polytetrafluoroethylene dispersion, 26-42 parts of silicon dioxide, 1-3 parts of defoaming agent, 1-5 parts of curing agent;
[0007] The raw materials of the first asphalt self-adhesive layer include the following components in parts by weight:
[0008] 60-80 parts of asphalt, 10-20 parts of styrene-butadiene-styrene copolymer, 2-24 parts of nitrile rubber, 3-10 parts of hydroxy polyester resin, 1-3 parts of antioxidant, and 1-3 parts of softener.
[0009] As a further technical solution, the weight ratio of the nitrile rubber to the hydroxy polyester resin is 1-2:1.
[0010] As a further technical solution, the silicon dioxide is trivalent carboxyl chlorovinyl resin modified silicon dioxide.
[0011] By using trivalent carboxyl chloroacetic resin to modify the surface of silica, the surface activity of silica is enhanced, improving the adhesion between the isolation layer and the concrete, and hydrogen bonding interaction is formed with the hydroxyl polyester resin in the first asphalt self-adhesive layer, thereby further improving the peeling strength performance between the pre-laid waterproof membrane and the post-poured concrete.
[0012] As a further technical solution, the preparation method of the ternary carboxylic chloroacetic resin modified silica comprises the following steps: adding the ternary carboxylic chloroacetic resin into ethyl acetate to obtain a ternary carboxylic chloroacetic resin solution, adding silica to the ternary carboxylic chloroacetic resin solution, stirring evenly, and concentrating to obtain the ternary carboxylic chloroacetic resin modified silica.
[0013] As a further technical solution, the weight ratio of the silica to the trivalent carboxyl chloroacetic acid resin is 4-13:1.
[0014] As a further technical solution, the mass fraction of the trivalent carboxyl chlorovinyl resin solution is 10% to 18%.
[0015] As a further technical solution, the raw materials of the second asphalt self-adhesive layer include the following components in parts by weight:
[0016] 60-80 parts of asphalt, 10-20 parts of styrene-butadiene-styrene copolymer, 1-3 parts of antioxidant, and 1-3 parts of softener.
[0017] As a further technical solution, the isolation layer is a PE film or a PET film; and the polyester tire base layer is a polyester fiber cloth.
[0018] As a further technical solution, the defoamer in the polymer coating is one or more of defoamer AF-3050, defoamer KS-603 and defoamer YL-801; the curing agent in the polymer coating is one or more of curing agent 593, curing agent T31 and curing agent S-100.
[0019] As a further technical solution, the antioxidant in the first asphalt self-adhesive layer is one or more of antioxidant 1076, antioxidant 1010 and antioxidant 697; the softener in the first asphalt self-adhesive layer is aromatic oil or rubber oil.
[0020] The present invention also provides a method for preparing a high-strength pre-laid waterproofing membrane, comprising the following steps:
[0021] S1. Weigh the raw materials of the polymer coating according to parts by weight, mix them evenly, and obtain a polymer coating mixture;
[0022] S2. Weigh the raw materials of the first asphalt self-adhesive layer according to parts by weight, mix them evenly, and obtain a first asphalt self-adhesive layer mixture;
[0023] S3, weighing the raw materials of the second asphalt self-adhesive layer according to parts by weight, mixing them evenly, and obtaining a second asphalt self-adhesive layer mixture;
[0024] S4, coating the first asphalt self-adhesive layer mixture and the second asphalt self-adhesive layer mixture on the upper and lower sides of the polyester tire base, respectively, and rolling them to obtain the first asphalt self-adhesive layer and the second asphalt self-adhesive layer respectively arranged on the upper and lower sides of the polyester tire base;
[0025] S5. Apply the polymer coating mixture on the first asphalt self-adhesive layer to obtain a polymer coating, and lay an isolation layer on the second asphalt self-adhesive layer to obtain a pre-laid waterproof membrane.
[0026] As a further technical solution, in steps S2 and S3, the mixing is carried out at a temperature of 180-195° C. and for a time of 3-5 hours.
[0027] As a further technical solution, the thickness of the polyester tread base layer is 1.0~1.8mm; the thickness of the polymer coating is 0.06~0.08mm; the isolation layer is a PE film with a thickness of 0.008~0.015mm; the thickness of the first asphalt self-adhesive layer is 0.8~1.5mm; the thickness of the second asphalt self-adhesive layer is 0.6~1.2mm.
[0028] The working principle and beneficial effects of the present invention are:
[0029] In the present invention, the first asphalt self-adhesive layer includes nitrile rubber and hydroxy polyester resin, and the synergistic effect of the two can effectively improve the peeling strength performance between the pre-laid waterproofing membrane and the post-cast concrete. In addition, the silicon dioxide added to the polymer coating can also improve the peeling strength performance between the pre-laid waterproofing membrane and the post-cast concrete. DETAILED DESCRIPTION
[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] In the following embodiments and comparative examples, the model of polytetrafluoroethylene dispersion is D-110; the particle size of silicon dioxide is 100 mesh; the asphalt is 90# asphalt; the model of styrene-butadiene-styrene copolymer is D1101 JU; the model of nitrile rubber is NBR 1052J; the model of hydroxy polyester resin is VOK-2776-TS; the model of trivalent carboxyl chloroacetic acid resin is SOLBINM5; the isolation layer is PE film with a thickness of 0.01 mm; the polyester base layer is polyester fiber cloth with a model of 120 g / m 2 Polyester cloth, thickness 1.6mm.
[0032] Example 1
[0033] A high-strength pre-laid waterproofing coiled material comprises a polymer coating, a first asphalt self-adhesive layer, a polyester base layer, a second asphalt self-adhesive layer and an isolation layer arranged in sequence from top to bottom. The raw materials of the polymer coating comprise the following components in parts by weight:
[0034] 30 parts of polytetrafluoroethylene dispersion, 26 parts of silicon dioxide, 1 part of defoamer KS-603, 1 part of curing agent S-100;
[0035] The raw materials of the first asphalt self-adhesive layer include the following components in parts by weight:
[0036] 60 parts of asphalt, 10 parts of styrene-butadiene-styrene copolymer, 2 parts of nitrile rubber, 3 parts of hydroxy polyester resin, 1 part of antioxidant 1010, 1 part of aromatic oil;
[0037] The raw materials of the second asphalt self-adhesive layer include the following components in parts by weight:
[0038] 60 parts of asphalt, 10 parts of styrene-butadiene-styrene copolymer, 1 part of antioxidant 1010, and 1 part of aromatic oil.
[0039] The preparation method thereof comprises the following steps:
[0040] S1. Weigh the raw materials of the polymer coating according to parts by weight, mix them evenly, and obtain a polymer coating mixture;
[0041] S2. Weigh the raw materials of the first asphalt self-adhesive layer according to parts by weight, and mix them at 180° C. for 5 hours to obtain a first asphalt self-adhesive layer mixture;
[0042] S3, weighing the raw materials of the second asphalt self-adhesive layer according to parts by weight, and mixing them at 180° C. for 5 hours to obtain a second asphalt self-adhesive layer mixture;
[0043] S4, coating the first asphalt self-adhesive layer mixture and the second asphalt self-adhesive layer mixture on the upper and lower sides of the 1.6 mm thick polyester tire base layer, respectively, and rolling forming, to obtain a 1.2 mm thick first asphalt self-adhesive layer and a 1.12 mm thick second asphalt self-adhesive layer respectively disposed on the upper and lower sides of the polyester tire base layer;
[0044] S5. Apply a polymer coating mixture on the first asphalt self-adhesive layer to obtain a 0.07 mm thick polymer coating, and lay a 0.01 mm thick isolation layer on the second asphalt self-adhesive layer to obtain a pre-laid waterproof membrane.
[0045] Example 2
[0046] A high-strength pre-laid waterproofing coiled material comprises a polymer coating, a first asphalt self-adhesive layer, a polyester base layer, a second asphalt self-adhesive layer and an isolation layer arranged in sequence from top to bottom. The raw materials of the polymer coating comprise the following components in parts by weight:
[0047] 40 parts of polytetrafluoroethylene dispersion, 35 parts of silicon dioxide, 2 parts of defoamer KS-603, 3 parts of curing agent S-100;
[0048] The raw materials of the first asphalt self-adhesive layer include the following components in parts by weight:
[0049] 70 parts of asphalt, 15 parts of styrene-butadiene-styrene copolymer, 5 parts of nitrile rubber, 7 parts of hydroxy polyester resin, 2 parts of antioxidant 1010, 2 parts of aromatic oil;
[0050] The raw materials of the second asphalt self-adhesive layer include the following components in parts by weight:
[0051] 70 parts of asphalt, 15 parts of styrene-butadiene-styrene copolymer, 2 parts of antioxidant 1010, and 2 parts of aromatic oil.
[0052] The preparation method thereof comprises the following steps:
[0053] S1. Weigh the raw materials of the polymer coating according to parts by weight, mix them evenly, and obtain a polymer coating mixture;
[0054] S2. Weigh the raw materials of the first asphalt self-adhesive layer according to parts by weight, and mix them at 190° C. for 4 hours to obtain a first asphalt self-adhesive layer mixture;
[0055] S3, weighing the raw materials of the second asphalt self-adhesive layer according to parts by weight, and mixing them at 190° C. for 4 hours to obtain a second asphalt self-adhesive layer mixture;
[0056] S4, coating the first asphalt self-adhesive layer mixture and the second asphalt self-adhesive layer mixture on the upper and lower sides of the 1.6 mm thick polyester tire base layer, respectively, and rolling forming, to obtain a 1.2 mm thick first asphalt self-adhesive layer and a 1.12 mm thick second asphalt self-adhesive layer respectively disposed on the upper and lower sides of the polyester tire base layer;
[0057] S5. Apply a polymer coating mixture on the first asphalt self-adhesive layer to obtain a 0.07 mm thick polymer coating, and lay a 0.01 mm thick isolation layer on the second asphalt self-adhesive layer to obtain a pre-laid waterproof membrane.
[0058] Example 3
[0059] A high-strength pre-laid waterproofing coiled material comprises a polymer coating, a first asphalt self-adhesive layer, a polyester base layer, a second asphalt self-adhesive layer and an isolation layer arranged in sequence from top to bottom. The raw materials of the polymer coating comprise the following components in parts by weight:
[0060] 50 parts of polytetrafluoroethylene dispersion, 42 parts of silicon dioxide, 3 parts of defoamer KS-603, 5 parts of curing agent S-100;
[0061] The raw materials of the first asphalt self-adhesive layer include the following components in parts by weight:
[0062] 80 parts of asphalt, 20 parts of styrene-butadiene-styrene copolymer, 24 parts of nitrile rubber, 10 parts of hydroxy polyester resin, 3 parts of antioxidant 1010, 3 parts of aromatic oil;
[0063] The raw materials of the second asphalt self-adhesive layer include the following components in parts by weight:
[0064] 80 parts of asphalt, 20 parts of styrene-butadiene-styrene copolymer, 3 parts of antioxidant 1010, and 3 parts of aromatic oil.
[0065] The preparation method thereof comprises the following steps:
[0066] S1. Weigh the raw materials of the polymer coating according to parts by weight, mix them evenly, and obtain a polymer coating mixture;
[0067] S2. Weigh the raw materials of the first asphalt self-adhesive layer according to parts by weight, and mix them at 195° C. for 3 hours to obtain a first asphalt self-adhesive layer mixture;
[0068] S3, weighing the raw materials of the second asphalt self-adhesive layer according to parts by weight, and mixing them at 195° C. for 3 hours to obtain a second asphalt self-adhesive layer mixture;
[0069] S4, coating the first asphalt self-adhesive layer mixture and the second asphalt self-adhesive layer mixture on the upper and lower sides of the 1.6 mm thick polyester tire base layer, respectively, and rolling forming, to obtain a 1.2 mm thick first asphalt self-adhesive layer and a 1.12 mm thick second asphalt self-adhesive layer respectively disposed on the upper and lower sides of the polyester tire base layer;
[0070] S5. Apply a polymer coating mixture on the first asphalt self-adhesive layer to obtain a 0.07 mm thick polymer coating, and lay a 0.01 mm thick isolation layer on the second asphalt self-adhesive layer to obtain a pre-laid waterproof membrane.
[0071] Example 4
[0072] The only difference between this embodiment and embodiment 2 is that 9 parts of nitrile rubber and 3 parts of hydroxyl polyester resin are added to the first asphalt self-adhesive layer.
[0073] Example 5
[0074] The only difference between this embodiment and embodiment 2 is that 6 parts of nitrile rubber and 6 parts of hydroxyl polyester resin are added to the first asphalt self-adhesive layer.
[0075] Example 6
[0076] The only difference between this embodiment and embodiment 2 is that 8 parts of nitrile rubber and 4 parts of hydroxyl polyester resin are added to the first asphalt self-adhesive layer.
[0077] Example 7
[0078] The only difference between this embodiment and embodiment 6 is that the silica is ternary carboxylic chloroacetic resin modified silica, and the preparation method of ternary carboxylic chloroacetic resin modified silica comprises the following steps: adding 9 parts of ternary carboxylic chloroacetic resin to ethyl acetate to obtain a ternary carboxylic chloroacetic resin solution with a mass fraction of 15%, adding 26 parts of silica to the ternary carboxylic chloroacetic resin solution, stirring evenly, and concentrating to obtain ternary carboxylic chloroacetic resin modified silica.
[0079] Example 8
[0080] The only difference between this embodiment and embodiment 6 is that the silica is ternary carboxylic chloroacetic resin modified silica, and the preparation method of ternary carboxylic chloroacetic resin modified silica comprises the following steps: adding 2 parts of ternary carboxylic chloroacetic resin to ethyl acetate to obtain a ternary carboxylic chloroacetic resin solution with a mass fraction of 15%, adding 33 parts of silica to the ternary carboxylic chloroacetic resin solution, stirring evenly, and concentrating to obtain ternary carboxylic chloroacetic resin modified silica.
[0081] Example 9
[0082] The only difference between this embodiment and embodiment 6 is that the silica is ternary carboxylic chloroacetic resin modified silica, and the preparation method of ternary carboxylic chloroacetic resin modified silica comprises the following steps: adding 7 parts of ternary carboxylic chloroacetic resin to ethyl acetate to obtain a ternary carboxylic chloroacetic resin solution with a mass fraction of 15%, adding 28 parts of silica to the ternary carboxylic chloroacetic resin solution, stirring evenly, and concentrating to obtain ternary carboxylic chloroacetic resin modified silica.
[0083] Example 10
[0084] The only difference between this embodiment and embodiment 6 is that the silica is ternary carboxylic chloroacetic resin modified silica, and the preparation method of ternary carboxylic chloroacetic resin modified silica comprises the following steps: adding 2.5 parts of ternary carboxylic chloroacetic resin to ethyl acetate to obtain a ternary carboxylic chloroacetic resin solution with a mass fraction of 15%, adding 32.5 parts of silica to the ternary carboxylic chloroacetic resin solution, stirring evenly, and concentrating to obtain ternary carboxylic chloroacetic resin modified silica.
[0085] Comparative Example 1
[0086] The only difference between this comparative example and Example 1 is that no nitrile rubber is added to the first asphalt self-adhesive layer, and 5 parts of hydroxyl polyester resin are added.
[0087] Comparative Example 2
[0088] The only difference between this comparative example and Example 1 is that no hydroxy polyester resin is added to the first asphalt self-adhesive layer, and 5 parts of nitrile rubber are added.
[0089] Comparative Example 3
[0090] The only difference between this comparative example and Example 1 is that no nitrile rubber and hydroxy polyester resin are added to the first asphalt self-adhesive layer, and 15 parts of styrene-butadiene-styrene copolymer are added.
[0091] Comparative Example 4
[0092] The only difference between this comparative example and Example 1 is that silicon dioxide is not added to the polymer coating.
[0093] The pre-laid waterproof membranes prepared in Examples 1 to 10 and Comparative Examples 1 to 4 were tested for peeling strength performance with post-cast concrete in accordance with GB / T 23457-2017 "Pre-laid Waterproof Membrane", wherein the specimens were immersed in water for 168 hours; and the specimens were heat treated at 70°C for 68 hours.
[0094] The test results are shown in Table 1 below:
[0095] Table 1 Test results
[0096]
[0097] Compared with Comparative Examples 1 to 3, the peeling strength performance of the pre-laid waterproofing membrane and the post-cast concrete of Example 1 is significantly improved, which indicates that the nitrile rubber and the hydroxy polyester resin in the first asphalt self-adhesive layer have a synergistic effect, which can effectively improve the peeling strength performance of the pre-laid waterproofing membrane and the post-cast concrete. Compared with Comparative Example 4, the peeling strength performance of the pre-laid waterproofing membrane and the post-cast concrete of Example 1 is significantly improved, which indicates that the addition of silica in the polymer coating can also improve the peeling strength performance of the pre-laid waterproofing membrane and the post-cast concrete.
[0098] Compared with Examples 2 and 4, the peeling strength performance of the pre-laid waterproofing membrane and the post-cast concrete of Examples 5 to 6 is significantly improved, which indicates that when the weight ratio of nitrile rubber and hydroxyl polyester resin in the first asphalt self-adhesive layer is 1 to 2: 1, the peeling strength performance of the pre-laid waterproofing membrane and the post-cast concrete can be further improved. Compared with Example 6, the peeling strength performance of the pre-laid waterproofing membrane and the post-cast concrete of Examples 7 to 10 is improved, which indicates that the ternary carboxyl chloroacetic resin modified silica can improve the peeling strength performance of the pre-laid waterproofing membrane and the post-cast concrete. In addition, compared with Examples 7 to 8, the peeling strength performance of the pre-laid waterproofing membrane and the post-cast concrete of Examples 9 to 10 is significantly improved, which indicates that when the weight ratio of silica and ternary carboxyl chloroacetic resin is 4 to 13: 1, the peeling strength performance of the pre-laid waterproofing membrane and the post-cast concrete can be further improved.
[0099] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A high-strength pre-laid waterproofing membrane, comprising a polymer coating, a first asphalt self-adhesive layer, a polyester base layer, a second asphalt self-adhesive layer and an isolation layer arranged in sequence from top to bottom, characterized in that: The raw materials of the polymer coating include the following components in parts by weight: 30-50 parts of polytetrafluoroethylene dispersion, 26-42 parts of silicon dioxide, 1-3 parts of defoaming agent, 1-5 parts of curing agent; The raw materials of the first asphalt self-adhesive layer include the following components in parts by weight: 60-80 parts of asphalt, 10-20 parts of styrene-butadiene-styrene copolymer, 2-24 parts of nitrile rubber, 3-10 parts of hydroxy polyester resin, 1-3 parts of antioxidant, and 1-3 parts of softener; The silicon dioxide is ternary carboxyl chlorovinyl resin modified silicon dioxide; The preparation method of the ternary carboxyl chloroacetate resin modified silica comprises the following steps: adding the ternary carboxyl chloroacetate resin into ethyl acetate to obtain a ternary carboxyl chloroacetate resin solution, adding silica into the ternary carboxyl chloroacetate resin solution, stirring evenly, and concentrating to obtain the ternary carboxyl chloroacetate resin modified silica.
2. A high-strength pre-laid waterproofing membrane according to claim 1, characterized in that: The weight ratio of the nitrile rubber to the hydroxy polyester resin is 1-2:
1.
3. The high-strength pre-laid waterproofing membrane according to claim 1, characterized in that: The weight ratio of the silicon dioxide to the trivalent carboxyl chloroacetic acid resin is 4-13:
1.
4. The high-strength pre-laid waterproofing membrane according to claim 1, characterized in that: The mass fraction of the ternary carboxyl chlorovinyl resin solution is 10% to 18%.
5. The high-strength pre-laid waterproofing membrane according to claim 1, characterized in that: The raw materials of the second asphalt self-adhesive layer include the following components in parts by weight: 60-80 parts of asphalt, 10-20 parts of styrene-butadiene-styrene copolymer, 1-3 parts of antioxidant, and 1-3 parts of softener.
6. The high-strength pre-laid waterproofing membrane according to claim 1, characterized in that: The defoamer in the polymer coating is one or more of defoamer AF-3050, defoamer KS-603 and defoamer YL-801; the curing agent in the polymer coating is one or more of curing agent 593, curing agent T31 and curing agent S-100.
7. The high-strength pre-laid waterproofing membrane according to claim 1, characterized in that: The antioxidant in the first asphalt self-adhesive layer is one or more of antioxidant 1076, antioxidant 1010 and antioxidant 697; the softener in the first asphalt self-adhesive layer is aromatic oil or rubber oil.
8. A method for preparing a high-strength pre-laid waterproofing membrane according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1. Weigh the raw materials of the polymer coating according to parts by weight, mix them evenly, and obtain a polymer coating mixture; S2. Weigh the raw materials of the first asphalt self-adhesive layer according to parts by weight, mix them evenly, and obtain a first asphalt self-adhesive layer mixture; S3, weighing the raw materials of the second asphalt self-adhesive layer according to parts by weight, mixing them evenly, and obtaining a second asphalt self-adhesive layer mixture; S4, coating the first asphalt self-adhesive layer mixture and the second asphalt self-adhesive layer mixture on the upper and lower sides of the polyester tire base, respectively, and rolling them to obtain the first asphalt self-adhesive layer and the second asphalt self-adhesive layer respectively arranged on the upper and lower sides of the polyester tire base; S5. Apply the polymer coating mixture on the first asphalt self-adhesive layer to obtain a polymer coating, and lay an isolation layer on the second asphalt self-adhesive layer to obtain a pre-laid waterproof membrane.
Citation Information
Patent Citations
Environment-friendly root-puncture-resistant modified asphalt waterproof coiled material and preparation method thereof
CN112745800A
Take waterproofing membrane of self -adhesive layer
CN207403292U